Management Leadership Head Schools in Improving Teacher Performancein School Base Country 1 Palembang - Lisnawati, Lisnawati; Lian, Bukman; Nugroho, Hery Setiyo (Journal of Social Science and Education Research, 2024)
Principal leadership management and teacher performance are two important elements for the success of education in schools, so research was conducted with the research objective of describing and analyzing principal leadership management in improving teacher performance at Palembang 1 State Elementary School. The results of the research concluded 1) the principal's leadership management had been implemented well in improving performance at SD Negeri 1 Palembang; 2) the principal's leadership management which is carried out includes: a) planning: the principal prepares an activity plan involving teachers and stakeholders such as supervisors, school committees and elements of the Education Service, b) Organizing: the principal organizes school resources such as infrastructure and facilities resources , financial resources, and human resources. c) mobilization: the principal provides opportunities for teachers to develop competencies according to teacher needs and d) supervision: the principal supervises technology-based teacher performance and supervision twice in one academic year; 3) the principal applies participatory, collaborative, teamwork leadership, provides examples of positive behavior and actions, motivates and encourages teachers to develop their competencies, is honest and open to communicating with teachers and other school members. The obstacles to principal leadership management in improving teacher performance at SD Negeri 1 Palembang are 1) lack of time and opportunity to directly develop teachers, 2) not optimal utilization of educational infrastructure, financing and supervision. Efforts to overcome obstacles are 1) encouraging teachers to utilize technology-based learning media, 2) planning the provision of facilities in stages and sustainably according to the school's financing capacity. 3) assigning one of the teachers to accompany every activity at the school as deputy principal.